Faktor-Faktor yang Berpengaruh pada Pertumbuhan Perusahaan Sektor Foods & Beverages yang Terdaftar di Bursa Efek Indonesia - Jacinta Winarto; Marcellia Susan (Syntax Literate, 2022)
Company growth is something that must be considered by food & beverage companies. With the increase in company growth during the COVID-19 pandemic, the question is what factors affect the company's growth. Judging from previous research and facts in the field, it is suspected that the influencing factors are marketing costs, company age, company size, research & development costs. This study aims to examine and analyze the effect of marketing costs, company age, company size, research & development costs on company growth. The population in this study are all food & beverage companies listed on the Indonesia Stock Exchange for the 2020-2021 period. Samples were taken using a purposive random method. Furthermore, this data was analyzed using a multiple linear regression model. the results of the research show that there is a positive influence from marketing costs and research & development costs. on company growth. The results of this study are intended to provide advice to food & beverages that marketing costs and research & development costs. must be considered to increase the growth of the company. Keywords: company growth; marketing cost; company age; company size; research and development